Procession of the Most Sacred Heart of Jesus: A Cultural Expression of Mena Vicariate Community Preserving the Image of Atambua Diocese - Lusius Tae Mau (International Journal Labs, 2026)
Religious rituals are important cultural expressions that preserve collective identity, social solidarity, and spiritual values within a community. Amid globalization and modernization, local religious traditions face challenges in maintaining their continuity, particularly among younger generations. The procession of the Sacred Heart of Jesus in the Mena Vicariate, Atambua Diocese, represents a unique interaction between Catholic spirituality and the cultural identity of the Atoni Pah Meto community. This study aims to analyze the procession of the Sacred Heart of Jesus as a cultural expression and its role in preserving the identity of the local church community in the Atambua Diocese. This research employed a qualitative approach with a socio-anthropological perspective. Data were collected through direct observation, documentation, statistical records from the Pastoral Center of the Atambua Diocese, and relevant literature studies related to religion, culture, and ritual practices. The findings reveal that the procession strengthens religious commitment and community identity through three main cultural dimensions: inclusiveness, symbolism, and intergenerational transmission. Statistical data indicate significant participation of the Mena Vicariate community, including 1,452 baptized members, 1,596 Eucharistic recipients, 269 marriage sacrament recipients, and 161 recipients of the Holy Oil sacrament in 2025. These findings demonstrate that the Sacred Heart of Jesus procession functions not only as a religious devotion but also as a cultural mechanism that preserves collective memory, strengthens social relationships, and maintains the identity of the Atambua Diocese. The study concludes that religious practices embedded within local culture play an essential role in sustaining faith, tradition, and community continuity amid social change.